The Podonominae pupae (Diptera: Chironomidae) of the tropical high Andean rivers - Acosta, Raúl; Prat, Narcís (Revista de Biología Tropical, 2018)
The Podonominae is a subfamily of Chironomidae which immature stages inhabit cold streams and brooks. In South America, most of the species have been reported only from the Andean/Patagonian subregion. However, the knowledge of its diversity from high tropical areas is still scarce. We studied the richness of genera and morphotypes of pupae and pupal exuviae of the subfamiliy Podonominae (Diptera: Chironomidae) in the high Andean rivers from Colombia, Ecuador and Peru, and discussed its geographical distribution in the studied area. The specimens were collected between 2004 and 2011 in 197 sampling points, from 17 basins over 2 000 m.a.s.l. During the dry season, benthic and drift samples were taken in different substrates. We recognized three genera: Podonomopsis, Parochlus and Podonomus, with one, nine and 14 morphotypes, respectively. Only six of them were clearly determined as species previously described. Podonomopsis was represented only by one species, P. illiesi, only found in high altitude rivers in Perú (above 3 500 m.a.s.l.). Morphotypes richness and abundance of Parochlus were higher in rivers from Ecuador and Colombia (P. incaicus, Parochlus sp. 1 and Parochlus sp. 2 were the most common species). Conversely, Podonomus was more diverse and abundant in rivers from Perú (P. caranqui, P. fittkaui and P. fastigians were the most common species). We found a clear pattern of distribution of morphotypes in the latitudinal gradient. First, we confirmed an evident decrease in the morphotypes richness in relation to the South Andes. Second, we found species such as Podomopsis illiesi, Podonomus fittkaui and Podomus fastigians that only were present in Perú, but not in Ecuador and Colombia. For these species, the Huancabamba Depression (6°S Latitude, North of Perú), a major structural and physiographic break in the Andes, could represent an important barrier in their dispersion toward lower latitudes. A taxonomic key to genera and morphotypes determination was also provided.